2013
DOI: 10.1074/jbc.m112.394064
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Oligosaccharides Inhibit Chemokine (CXC Motif) Ligand 12 (CXCL12) Cardioprotection by Binding Orthogonal to the Dimerization Interface, Promoting Oligomerization, and Competing with the Chemokine (CXC Motif) Receptor 4 (CXCR4) N Terminus

Abstract: Background: GAG/CXCL12 interactions are critical for chemokine function but co-administration may abrogate their individual cardioprotective effects in a clinical setting. Results: Biophysical studies distinguish CXCL12 residues involved in dimerization from those likely to contact heparin directly. Conclusion: CXCL12 dimerization is required for high affinity heparin binding and protects N-terminal degradation. Significance: Knowledge of the GAG-binding site will enable future development of heparin-insensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
83
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 44 publications
9
83
1
Order By: Relevance
“…We used the hCXCL1 dimer (PDB code 1MGS) and heparin 12-mer (PDB code 1HPN) structures to generate the HADDOCK models. a similar observation of competition between N-domain and GAG binding and proteolytic protection in the GAG-bound form has been reported (41).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…We used the hCXCL1 dimer (PDB code 1MGS) and heparin 12-mer (PDB code 1HPN) structures to generate the HADDOCK models. a similar observation of competition between N-domain and GAG binding and proteolytic protection in the GAG-bound form has been reported (41).…”
Section: Discussionsupporting
confidence: 57%
“…X-ray structures could be determined only of a disaccharide-bound chemokine (38,39). Although NMR characterization of binding of disaccharides posed no problems, characterizing longer oligosaccharides seems to depend on the chemokine, with some giving good spectra and others precipitating even for a tetrasaccharide (26,32,40,41). We obtained excellent NMR spectra for hCXCL1, and, more significantly, our observation of two distinct non-overlapping GAG binding domains is novel.…”
Section: Discussionmentioning
confidence: 51%
“…2A and 7C). It has also been shown that GAG binding increases the lifetime of CXCL12 by protecting it from enzymatic cleavage (31,62). These observations suggest that NAC monomer-dimer equilibrium and GAG binding interactions and affinities must be highly regulated and that any disruption, such as proteolytic cleavage, impairs dimerization and GAG binding, which, in turn, disrupts chemokine gradient and neutrophil recruitment, enabling microbes to evade the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Two x-ray structures of chemokine-disaccharide are known, and most NMR structural studies also report only disaccharide binding, which provides only limited insights (46,47). However, NMR studies have had better success with longer GAGs, but the extent of the structural insights varies among different chemokines and seems to be critically dependent on experimental conditions (21,31,48). Recent studies by Handel and co-workers (21) on CCL27 and Volkman and co-workers (31) on CXCL12 using different oligosaccharides, protein concentrations, protein:GAG ratios, and variants (monomer and dimer) have shown that chemokine structural plasticity, oligomerization properties, GAG length, and binding-induced oligomerization/aggregation/precipitation are intimately coupled.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, application of N-terminally truncated CXCL12 variants induced HPC mobilization, with CXCL12 and CXCL12 demonstrating a significant effect on HPC mobilization. In addition to the putative antagonistic mechanism for CXCL12 as mentioned earlier, competition with biologically active CXCL12 for binding to GAG chains of proteoglycans along the endothelial surface might be responsible for the mobilization of HPCs [7,54]. The excess of N-terminally processed CXC12, although demonstrating a reduced affinity for Heparin, would be sufficient for a relevant displacement of active CXCL12.…”
Section: Discussionmentioning
confidence: 99%